The regulatory system and subjectivity in a Nahuat community. An invisibilized community regulatory density. Issue 1 (1st January 2019) - Sánchez-Acevedo, Eliel Francisco; Sánchez-Díaz de Rivera, Ma. Eugenia
ABSTRACT: The primary objective of this article is to provide an in-depth interpretation of the Nahuat indigenous community's regulatory system in San Miguel Tzinacapan (Puebla, Mexico) through approaches such as the Sociology of Absences, the Actor-Network Theory (ANT), and the Ontological Turn. The research carried out in the locality demonstrates that San Miguel Tzinacapan has its own autonomous and operational regulatory system. This system contains elements of the pre-Hispanic civilizing matrix: including systems such as that of witchcraft/healing and crimes against nature, as well as the Catholic-colonial model present in the ceremonial cycle and "cargo system." This regulatory system functions as a framework that helps sustain the agency of Tzinacapan. The relationship between the subjectivity and regulatory system of the Nahuat population, with the subjectivity of positive law, has demonstrated to have a conflicting nature. In Mexico, indigenous regulatory bodies have been defined and considered as "customs and practices" (usos y costumbres) or "customary laws" by legal science, thus stripping them of the quality of valid and current law, and denying them as valid knowledge. This is due to the fact that the indigenous normative matrix has been depicted as a "non-law" while the subjectivity that underlies it is ruled as inferior. This article presents an in-depth analysis of the Tzinacapan regulatory system characteristics, as well as the underlying subjectivity in contrast with that of positive law.